Anxiety Against Covid-19 With A Planning Family Acceptor Visit - Kiki Lesdianti; Ira Kusumawaty; Siti Hindun; Desy Setiawati; Aprillia Ayu SY (Journal of Maternal and Child Health Sciences (JMCHS), 2022)
The pandemic Covid-19 caused a decrease in the number of family planning acceptors in Indonesia and particularly in Palembang which will have an impact on pregnancy rates were rising and the Baby Boom phenomenon occurred in Indonesia. Purpose: This study aims to analyze anxiety during Covid-19 in family planning acceptors and analyze the relationship between anxiety and Covid-19 with family planning acceptor visits at the Palembang City Health Center in 2021. Method: The research design used is correlation analytic with a cross-sectional design. The sampling technique in this study used a purposive sampling technique (Non-Probability ). The sample of this study amounted to 104 respondents from 140 populations. Data collection was carried out in the working area of ​​the Ariodillah Health Center and the Pembina City of Palembang by using direct questionnaires and online questionnaires using Google Forms This research was conducted on 17 May – 03 June 2021. The data analysis used was the non-linear regression test. Result: sig values 0.832 > probability of 0,05 it is stated that no relationship exists significant between Anxiety against Covid 19 to visiting family planning acceptors. Based on the comparison of the t arithmetic value of 0.213 < t table value of 1.663, it can be concluded that H1 or the first hypothesis is rejected. This means that there is no relationship between anxiety about COVID-19 and the visit of family planning acceptors at the Palembang City Health Center. Conclusion: There is no significant relationship between anxiety about Covid-19 and the visit of family planning acceptors at the Palembang City Health Center.